Safety and immunogenicity of human neonatal RV3 rotavirus vaccine (Bio Farma) in adults, children, and neonates in Indonesia: Phase I Trial. Issue 33 (30th July 2021) - At Thobari, Jarir; Damayanti, Wahyu; Haposan, Jonathan Hasian; Nirwati, Hera; Iskandar, Kristy; Samad,; Fahmi, Julianita; Sari, Rini Mulia; Bachtiar, Novilia Sjafri; Watts, Emma; Bines, Julie E.; Soenarto, Yati
Abstract: Background: Despite safe and effective WHO prequalified rotavirus vaccines, at least 84 million children remain unvaccinated. A birth dose schedule of the RV3-BB vaccine was reported to be highly efficacious against severe rotavirus disease in Indonesian infants and is under further development at PT Bio Farma, Indonesia. The aim is to develop a rotavirus vaccine starting from birth that could improve the implementation, safety, and effectiveness of vaccines. Methods: A multi-site phase I study of a human neonatal RV3 rotavirus vaccine (Bio Farma) in adults, children, neonates in Indonesia from April 2018 to March 2019. The adult and child cohorts were open-labeled single-dose, while the neonatal cohort was randomized, double-blind, and placebo-controlled three-doses at the age of 0–5 days, 8–10 weeks, and 12–14 weeks. The primary objective was to assess the safety of vaccines with the immunogenicity and vaccine virus fecal shedding as the secondary endpoints in neonates. Results: Twenty-five adults, 25 children, and 50 neonates were recruited, and all but one in the neonatal cohort completed all study procedures. Three serious adverse events were reported (1 adult & 2 neonates), but none were assessed related to investigational product (IP). The neonatal vaccine group had a significantly higher positive immune response (cumulative seroconverted SNA and IgA) 28 days after three doses than those in the placebo group (72% vs. 16.7%, respectively). The GMT of serum IgA in the vaccine group was significantly higher at post IP dose 1 (p < 0.05) and post IP dose 3 (p < 0.001) compared to the placebo group. Conclusion: The trial results show that the RV3 rotavirus vaccine (Bio Farma) is well tolerated in all participant cohorts (adults, children, and neonates). Three doses of this vaccine administered in a neonatal schedule were immunogenic. These promising results support further clinical development of the RV3 rotavirus vaccine (Bio Farma).